A Study On Stylistic Devices Employed In English And Vietnamese Film Titles – A Context-Based Perspective - Thái Thị Phương Lan (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
This study is aimed to study on stylistic devices employed in English and Vietnamese film titles and find out the similarities and differences between them. It is also hoped to provide those who have interest in linguistic features used in the title of films in particular with useful information. Moreover, this study aims at considering what is behind the similarities and differences in comparison in terms of linguistic and, if possible, cultural features. The data for analysis in this thesis are 300 samples collected from film websites in English and Vietnamese. The data were described and contrastively analyzed on stylistic aspects under qualitative and quantitative approaches. On the basis of a contrastive analysis, the thesis tries to find out stylistic devices employed in English and Vietnamese film titles in terms of phonetic, lexical and syntactical stylistic devices. With a hope of contributing to better teaching and learning English as a foreign language, especially to better the awareness of learners in understanding, translating and writing a catchy title, some suggested ideas were also included.